Collection analysis on social work: a cost-effective approach. Issue 2 (7th April 2015) - Liu, Maggie
Abstract : Purpose: – The purpose of this paper is to ensure the provision of effective library support to the scholarly community in areas of collection development and management. Last year, the author's library made the first attempt to conduct a collection evaluation on a multidisciplinary subject – social work. Design/methodology/approach: – In view of extensive subject coverage of a cross-disciplinary subject and the library's constraints, a cost-effective and manageable strategy using internal resources was used. The focus of the study was to concentrate on core subject areas of social work. By making use of circulation statistics of those areas, adequacy, strengths and weaknesses of the collection would be identified. Findings: – A positive adequacy of the social work collection was evidenced from a high usage of the collection. An in-depth study on the two major active sections, DDC 361 (social problems and services) and DDC 362 (social work for different groups of people), was also undertaken. Specific subject areas for improvement were identified. Originality/value: – Through conducting the project, it not only directly served the main purpose of enhancing the quality of the collection in alliance with the development of academic departments, but also expanded our subject knowledge. It is hoped that our experience can offer tips and stimulant for other libraries contemplating collection analysis on a multidisciplinary subject under restricted resources.